Who the Hell is Müller-Brockmann? : Conversations about the Swiss Style - Conrad, Demian; Cashmira Kakar, Aviva; Shaughnessy, Adrian; Beck, David Kilian (Salenstein : Niggli, 2022)
Müller-Brockmann, Josef ; Maag, Bruno ; Muggeridge, Fraser ; Sack, Freda ; Jacobs, Holger ; Jannuzzi, Michele ; Hollis, Richard ; Kinross, Robin ; De Bondt, Sara
boek